Different subsets of haematopoietic cells and immune cells in bone marrow between young and older donors. (21st October 2020) - Yao, W-L; Wen, Q; Zhao, H-Y; Tang, S-Q; Zhang, Y-Y; Wang, Y; Xu, L-P; Zhang, X-H; Huang, X-J; Kong, Y
Summary: Young donors are reported to be associated with better transplant outcomes than older donors in allogeneic hematopoietic stem cell transplantation (allo-HSCT), but the mechanism is still unclear. The current study compared the different subsets of haematopoietic stem cells (HSCs) and their progenitors as well as immune cells in bone marrow (BM) between young and older donors. The frequencies of HSCs, multipotent progenitors (MPPs) and myeloid progenitors, including common myeloid progenitors (CMPs) and megakaryocyte–erythroid progenitors (MEPs), were decreased, whereas those of lymphoid progenitors, including multi-potent lymphoid progenitors (MLPs) and common lymphoid progenitors (CLPs), were increased in the BM of young donors compared with in that of older donors. Lower reactive oxygen species (ROS) levels were observed in BM HSCs and six progenitor lines in young donors. Furthermore, young donors demonstrated higher frequencies of naive T cells and immune suppressor cells, such as alternative macrophages (M2) and lower frequencies of memory T cells and immune effectors, including T helper-1 and T cytotoxic-1 cells, in BM than older donors. Multivariate analysis demonstrated that donor age was independently correlated with BM HSC frequency. Although further validation is required, our results suggest that the differences in the frequency and immune differentiation potential of HSCs in BM between young donors and older donors may partly explain the different outcomes of allo-HSCT. Graphical Abstract: